FROM THE MARGINS TO THE MAINSTREAM: INDIGENISED DEVELOPMENT IN BORNEO WITH INFORMATION AND COMMUNICATION TECHNOLOGIES AND ITS CONTRIBUTION TO GLOBAL SUSTAINABLE DEVELOPMENT - Poline, Bala; Narayanan, Kulathuramaiyer; Harris, Roger W. (UNIMAS Publisher, 2020)
The introduction of Information and Communication Technologies (ICTs) to remote and isolatedindigenous communities in the forested interior of Borneo has generated desirable development benefitsfor them as well as revealing the processes of community engagement that were necessary for bringingthem about. Associated learning has also highlighted aspirations for development that relate to thespecifics of their cultures and lifestyles in relation to the natural environment in which they live, lendingcredence to the concept of ethno or indigenised development in contrast to notions of asset exploitationexpressed within orthodox development. The emergence of the global Sustainable Development Goals(SDGs) with their imperatives for protecting biodiversity and the rainforests as well as combatting climate change focusses greater attention on the role of indigenous peoples as stewards of fragile ecosystemsthat are highly susceptible to global warming. The experiences of applying ICTs to indigenised development within Borneo’s rainforest communities - helping them maintain eco-friendly lifestyles,conserve biodiversity and record their traditional knowledge about the climate - carries lessons of global significance for the wider achievement of the SGDs and the future of our planet.